2021
DOI: 10.3389/fonc.2020.580045
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Human Epidermal Growth Factor Receptor-2 Status and Programmed Cell Death Protein-1 Ligand Is Associated With Prognosis in Gastric Cancer

Abstract: BackgroundPD-L1 and HER-2 are routine biomarkers for gastric cancer (GC). However, little research has been done to investigate the correlation among PD-L1, HER-2, immune microenvironment, and clinical features in GC.MethodsBetween January 2013 and May 2020, a total of 120 GC patients treated with chemotherapy were admitted to Henan Tumor Hospital. We retrospectively identified PD-L1, HER-2 level before chemotherapy and abstracted clinicopathologic features and treatment outcomes. Univariate and multivariate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…A significant prognostic value of ERBB2 CN, TMB and genomic alterations associated with HER2 signaling could not be confirmed in this cohort. PD-L1 expression has been found to co-occur with HER2-positivity in 25-85% of GC/GEJ patients [21][22][23]32]. With 47.3% of HER2+/PD-L1+ patients, our result falls within the reported range.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A significant prognostic value of ERBB2 CN, TMB and genomic alterations associated with HER2 signaling could not be confirmed in this cohort. PD-L1 expression has been found to co-occur with HER2-positivity in 25-85% of GC/GEJ patients [21][22][23]32]. With 47.3% of HER2+/PD-L1+ patients, our result falls within the reported range.…”
Section: Discussionsupporting
confidence: 77%
“…In the study by Lian et al, combined HER2 and PD-L1 positivity was associated with improved overall survival in resectable GC [22]. In contrast, Lv et al showed that HER2+/PD-L1+ GC patients had inferior survival compared with HER2-/PD-L1patients [32]. The authors speculated that immunotherapy would be less suitable for HER2positive GC, which is controversial since the first interim analysis of the KEYNOTE-811 demonstrated an increased response rate of HER2-positive mGC/mGEJC patients to trastuzumab and pembrolizumab combined with chemotherapy [21].…”
Section: Discussionmentioning
confidence: 98%
“…Yang et al [14] found more tumor infiltration lymphocytes (TILs) in Her-2-positive regions of breast cancer tumor cells than in Her-2-negative expression regions. In this study, we found that Her-2 positive patients tended to have lower differentiation and higher tumor grade, which may be related to the high expression of CD4+ T cells as well as the relatively low expression of CD8+ T cells in the tumor stroma of the Her-2 positive group [16]. Furthermore, Yang et al [17,18] have confirmed that Her-2 positivity is usually indicative of EC with high proliferation and low differentiation.…”
Section: Discussionsupporting
confidence: 56%
“…Given the widespread use of immune checkpoint blockade therapies in gastrointestinal tumors [23][24][25]57 , we sought to determine whether there were distinct immune inhibitory checkpoints among three HER2 groups. To achieve this, we compared the RNA expression levels of key immune inhibitory and stimulatory checkpoint genes, along with their paired ligands and receptors 58 , between tumor and NAT in each HER2 group (Figure 5E).…”
Section: Distinct Tumor Immune Microenvironment and Immune Checkpoint...mentioning
confidence: 99%
“…Currently, HER2 targeted therapy has become a vital treatment option for certain types of gastroesophageal cancers, including esophageal Adenocarcinoma (EAC), GCA, GNCA, and stomach adenocarcinoma (STAD), particularly in advanced or metastatic cases 20, 23,24 . Anti-HER2 targeted therapies have improved survival outcomes in advanced gastroesophageal cancer patients with HER2 overexpression [23][24][25] . However, the relatively low prevalence (less than 30%) of HER2-positive cases poses challenges [26][27][28] , particularly for HER2-negative patients.…”
Section: Introductionmentioning
confidence: 99%